Enhancing Social Skills in University Students through Strengths-Based Counseling: A Literature Review Utilizing the Strengths Perspective Framework - Fatimah, Siti; Ahman, Ahman; Suherman, Uman; Ilfiandra, Ilfiandra (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
Strength-based counseling are grounded in the principles of positive psychology, emphasizing the recognition and development of individual strengths to enhance personal and interpersonal achievement. This approach fosters self-awareness and better relationships by encouraging individuals to recognize their strengths and those of others. Research indicates that a strengths-based approach can lead to a 50% increase in social relationships. The theory encompasses ten key propositions, including the ability to adapt and self-improve, the relationship between strengths and basic psychological needs, and the capacity for ongoing strength development influenced by various factors. Additionally, it highlights the variability of strength levels based on environmental context, the dialectical nature of strengths arising from challenges, and the importance of encouragement and effort recognition in motivating change. Ultimately, this model reinforces the significance of hope as a catalyst for transforming dysfunctional behaviors, fostering resilience, and promoting social competence.